2021
DOI: 10.1016/j.solmat.2020.110899
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the surface passivation mechanism during the fabrication of ex-situ doped poly-Si(B)/SiOx passivating contacts for high-efficiency c-Si solar cells

Abstract: Passivating the contacts of crystalline silicon (c-Si) solar cells (SC) with a poly-crystalline silicon (poly-Si) layer on top of a thin silicon oxide (SiOx) is currently sparking interest for reducing carrier recombination at the interface between the metal electrode and the c-Si substrate. However, due to the interrelation between different mechanisms at play, a comprehensive understanding of the surface passivation provided by the poly-Si/SiOx contact in the final SC has not been achieved yet. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Compared to the as-deposited samples, the passivation characteristics under the thermal annealing process showed an improvement in i V OC for all samples. This is attributed to the enhanced crystallinity of the poly-Si layer and field-effect passivation by the dopant in-diffusion and activation as well as the reduced interface state density 2 , 14 , 17 , 18 , 30 , 31 . For both groups of samples, as T PDA was increased, i V OC increased and reached the maximum; subsequently, i V OC decreased for higher T PDA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the as-deposited samples, the passivation characteristics under the thermal annealing process showed an improvement in i V OC for all samples. This is attributed to the enhanced crystallinity of the poly-Si layer and field-effect passivation by the dopant in-diffusion and activation as well as the reduced interface state density 2 , 14 , 17 , 18 , 30 , 31 . For both groups of samples, as T PDA was increased, i V OC increased and reached the maximum; subsequently, i V OC decreased for higher T PDA .…”
Section: Resultsmentioning
confidence: 99%
“…The passivation property of the selective contact deteriorates at high T PDA because of the following three reasons: First, the excessive in-diffusion of boron atoms into the silicon substrate forms an extended p-type region in the n-type substrate, following which the p-type flat-band region across the oxide greatly suppresses the field-effect passivation at the oxide region 30 , 31 . Second, the high concentration of the diffused boron atoms introduces an elevated Auger recombination rate 17 , 18 . Third, the increase of the aforementioned unpassivated surface area of the c-Si caused by the damage in SiO x also deteriorates the passivation.…”
Section: Resultsmentioning
confidence: 99%
“… 36 , 39 For chemically grown SiO x layers similar to the ones used in this study, such a disruption of the SiO x layer was already observed to occur after annealing at T ∼ 800–900 °C. 18 , 36 , 40 More particularly, in ref ( 18 ), Figure 2 presents TEM analyses of samples processed in our lab, in a similar way than the ones of interest here. Through these TEM analyses, we observed that the disruption of the SiO x interface occurred after long-annealing in between 800 °C and 900 °C, which is in good agreement with the temperature at which we observed XRR fringes vanishing in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Other than crystallization and doping activation, such high-temperature annealing has been shown to cause a shallow diffusion of dopants into the underlying c-Si substrate (and thus through the thin SiO x layer) as well as chemical/structural changes of the thin SiO x . 17 19 Moreover, lately, several studies have emphasized the detrimental impact of firing on the surface passivation properties provided by poly-Si contacts. 20 22 It is worth noting that in the currently foreseen integration of poly-Si contacts in c-Si solar cells, it is most likely that poly-Si contacts will be submitted to a firing process applied at the very end of the solar cell fabrication to contact the metal paste to the c-Si and/or poly-Si layer.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline (monocrystalline and polycrystalline) silicon [32] is surely the dominant technology for solar cells, representing a good compromise between performance and cost [20]. Excellent efficiencies over 25% are achieved by monocrystalline silicon technology [19], thanks to efficiency improving strategies, such as carrier recombination reduction through contact passivation [33], [34], [35], [36]. Even though these latest efficiency enhancing techniques are not commonly findable in the marketplace yet, monocrystalline silicon solar cells remain the preferable solution for powering a small outdoor electronic utility, like the application presented in this paper, with the minimum encumbrance and at a very reasonable cost.…”
Section: Solar Energy Harvestingmentioning
confidence: 99%